A critical review on Pulicaria species occurring in Qatar: traditional uses, phytochemistry and biological activities - Deepak M. Kasote (9562957) (2024)
In Qatar, three main species of Pulicaria (from Asteraceae) such as Pulicaria undulata (L.) C.A.Mey, Pulicaria gnaphalodes (Vent.) Boiss. and Pulicaria sicula (L.) Moris are reported. Traditionally, these species have almost the same ethnomedical uses, including their use as herbal tea. This could be because of morphological similarities among some of these species, which also results in taxonomic ambiguity. Altogether, this indicates that these species need to be reviewed comparatively, to understand the phytochemical uniqueness and therapeutic significance of each species individually, including species differentiation at the subspecies level. Hence, this review aims to comparatively review the available literature about traditional uses, phytochemistry, and bio-activities of these species. Being aromatic plants, the chemical composition of essential oils of these species has been extensively studied and reported over 300 volatile organic compounds. Among these, oxygenated monoterpenes and sesquiterpenes are dominant. The diverse and distinguishable composition of essential oils can differentiate P. undulata and Pulicaria crispa (Forssk.) Oliv. (Synonyme: Pulicaria undulata subsp. undulata). Likewise, flavonoids and sesquiterpenes are the most reported classes of compounds in non-essential oil fractions. Various biological and pharmacological activities are reported to the essential oils, crude extracts, and their fractions, or isolated compounds of these species. Among these, antimicrobial, anticancer, and anti-oxidant activities were mostly investigated, mainly under in vitro conditions. Several distinguishable compounds are listed for each species that can potentially be used as chemical markers while characterizing these species. Most of the traditional claims of these species are validated in recent scientific studies. However, further detailed in vivo clinical interventions are needed for their potential use as therapeutic agents. Other Information Published in: Phytochemistry Reviews License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11101-024-09932-0